2007
DOI: 10.1194/jlr.m600549-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid synthesis from α-linolenic acid by rat brain is unaffected by dietary n-3 PUFA deprivation

Abstract: Rates of conversion of a-linolenic acid (a-LNA, 18:3n-3) to docosahexaenoic acid (DHA, by the mammalian brain and the brain's ability to upregulate these rates during dietary deprivation of n-3 polyunsaturated fatty acids (PUFAs) are unknown. To answer these questions, we measured conversion coefficients and rates in post-weaning rats fed an n-3 PUFA deficient (0.2% a-LNA of total fatty acids, no DHA) or adequate (4.6% a-LNA, no DHA) diet for 15 weeks. Unanesthetized rats in each group were infused intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
121
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 55 publications
15
121
0
2
Order By: Relevance
“…DHA may be obtained directly from dietary sources, such as fish or fish products, or it can be synthesized from its nutritionally essential plant-derived precursor, α-linolenic acid (18:3n-3, α-LNA), through a series of elongation and desaturation steps (Sprecher 2000). The major site of DHA synthesis is the liver, whereas brain or heart synthesis is much less (Scott and Bazan 1989;Demar et al 2005;Igarashi et al 2007;Igarashi et al 2008;Rapoport et al 2010).…”
mentioning
confidence: 99%
“…DHA may be obtained directly from dietary sources, such as fish or fish products, or it can be synthesized from its nutritionally essential plant-derived precursor, α-linolenic acid (18:3n-3, α-LNA), through a series of elongation and desaturation steps (Sprecher 2000). The major site of DHA synthesis is the liver, whereas brain or heart synthesis is much less (Scott and Bazan 1989;Demar et al 2005;Igarashi et al 2007;Igarashi et al 2008;Rapoport et al 2010).…”
mentioning
confidence: 99%
“…Although high ALA intake drastically increased the ALA content in plasma lipids (an increase of the proportion from 6 1% to 10%), which is a reflection of the increase of ALA content in liver (Table 4), the ALA and DHA contents in frontal cortex and hippocampus did not increase (Tables 5 and 6). Other studies in rat brain showed that ALA after uptake from the circulation across the blood-brain barrier will be mainly oxidized and only a small fraction is converted to DHA (DeMar et al, 2005;Igarashi et al, 2007b). The activity of desaturation and elongation are higher in liver in comparison with brain (Igarashi et al, 2007a).…”
Section: Brainmentioning
confidence: 94%
“…Small fractions of LA and alpha-linolenic acid in the brain are converted to arachidonic acid (20:4n-6, AA) and docosahexaenoic acid (22:6n-3, DHA), respectively [41,42]. Besides, the alternations in the level of LA, the levels of dihomo-gamma-linolenic acid (20:3n-6) remained unchanged among all experimental groups.…”
Section: Discussionmentioning
confidence: 81%